Delineating the impact of executive dysfunction on social cognition for patients and caregivers in Amyotrophic Lateral Sclerosis - Burke, Tom M. J. (Trinity College (Dublin, Ireland). Institute of Neuroscience, 2016)
Amyotrophic Lateral Sclerosis (ALS) is a rapidly progressive neurodegenerative disease that implicates both motor and cognitive function, and is the most prevalent Motor Neuron Disease (MND). ALS is a clinically heterogeneous disease, one that requires detailed neuropsychological assessment to clarify the presenting cognitive phenotype of the disease. The main aim of this thesis was to investigate the impact of ALS on social cognitive processes, while considering other cognitive functions known to decline in some patients i.e., executive function.
Keywords: Neuropsychology, Ph.D.; PhD Trinity College Dublin, 2016